Crossing Borders, Drawing Boundaries : The Rhetoric of Lines across America - Wojahn, Patti; Couture, Barbara (Book collections on Project MUSE., 2016)
"A timely rhetorical exploration of divisionary bounds that divide an Us from a Them. To see anew the many lines that unite, divide, and define us, the essays highlight how discourse at borders and boundaries can create or thwart conditions for establishing identity and admitting difference"--Provided by publisher